PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DEWAN KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2019-2022 - Muhningtiyasari, Djuliana; Andini, Rita; Lestari, Utami Puji (STIE Semarang, 2024)
This study aims to analyse the effect of profitability, liquidity, leverage, independent board of commissioners, and audit committee on tax avoidance by using the dependent variable in the form of tax avoidance as measured using the cash effective tax rate (CETR). This study chose the object of research in the form of financial reports from property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The number of research samples was 25 companies obtained by purposive sampling method with data analysis techniques using multiple linear regression analysis. The results of the analysis show that profitability has a negative effect on tax avoidance and leverage has a positive effect on tax avoidance. While the variables of liquidity, independent board of commissioners, and audit committee have no effect on tax avoidance.